A Review of Security Threats by The Unauthorized in The E-Learning - Saleh, Mohamed Munser (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Computers have become an integral part of our everyday existence. They are used to store and to send among studentsâ€™ letters and sensitive documents, materials. In today's focused world, each Organization is endeavoring to enhance its proficiency and guarantee the nature of data asset. Computer networking technologies - intranet, web - have progressed to the point where data can be put away, transmitted, and available to people accessing the resource anytime and from anywhere.Â  These advantages additionally push organizations into executing web based innovation without considering the security dangers that this involves.